Association of state and trait anxiety with oral health status among adult dental patients: State and Trait Anxiety with Oral Health Status - Veeraboina, Nagarani; Doshi, Dolar; Kulkarni, Suhas; Patanapu , Shiva Kumar; Dantala, Satya Narayana; Adepu, Srilatha (Acta Biomedica Atenei Parmensis, 2020)
Background: Dental caries and periodontal diseases are the most prevalent oral health problems worldwide. Behavioral and psychosocial factors along with social, economic and cultural conditions may alter the health balance, favoring the onset of dental diseases. Hence the study was conducted to assess the association of state and trait anxiety with oral health status among adult dental patients. Methods: The study was carried out among 456 adult dental patients visiting Panineeya Institute of Dental Sciences and Hospital, Hyderabad. Anxiety levels were measured by State-Trait Anxiety Inventory-short version (STAI-S) consisting subscales State Anxiety (SA) and Trait Anxiety (TA). Clinical examination was done using WHO Basic Oral Health survey assessment form, 2013. The data was analyzed using Statistical Package for Social Sciences Software 21.0. p≤0.05 was considered statistically significant. Results: A significant gender difference (p=0.001) was noted for total anxiety with higher mean score observed among males (46.13±5.98) than females (45.32±6.00).Similarly, significant higher mean score was observed among males (23.31±4.08) than females (p=0.03) for State anxiety. Females had higher mean DMFT (3.61±3.21), DT (2.04±2.05), FT (0.49±1.34) and MT (1.08±2.09) components but significant difference was noted only for overall DMFT (p=0.03) and DT (p=0.001) component than males. Conclusion: Gender, education and previous dental visits didn’t show any significant association with total anxiety, state and trait anxiety. Likewise, none of the oral parameters showed any significant association except for the Decayed Teeth (DT) component of DMFT with total anxiety levels among study subjects.